2011
DOI: 10.1128/jvi.05576-11
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Excitotoxicity Is Involved in the Induction of Paralysis in Mice after Infection by a Human Coronavirus with a Single Point Mutation in Its Spike Protein

Abstract: Human coronaviruses (HCoV) are recognized respiratory pathogens, and some strains, including HCoV-OC43, can infect human neuronal and glial cells of the central nervous system (CNS) and activate neuroinflammatory mechanisms. Moreover, HCoV-OC43 is neuroinvasive, neurotropic, and neurovirulent in susceptible mice, where it induces chronic encephalitis. Herein, we show that a single point mutation in the viral spike (S) glycoprotein (Y241H), acquired during viral persistence in human neural cells, led to a hind-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…Disappearance of respiratory tract disease was observed for SARS-CoV in which E PBM was abrogated, preventing interaction of the viral protein with the PDZcontaining protein syntenin Regla-Nava et al, 2015). The absence of neurological symptoms following infection by either rOC/E stop or rOC/E-PBM D82A-V84A could potentially be linked to glutamate excitotoxicity that we have previously observed in mice (Brison et al, 2011), possibly by interfering with PDZ-domain containing proteins found in neuronal cells (Feng and Zhang, 2009). We also demonstrate that HCoV-OC43 putative TMD plays a role in the neuropathogenesis following the CNS infection, albeit to a lesser extent than its PBM.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Disappearance of respiratory tract disease was observed for SARS-CoV in which E PBM was abrogated, preventing interaction of the viral protein with the PDZcontaining protein syntenin Regla-Nava et al, 2015). The absence of neurological symptoms following infection by either rOC/E stop or rOC/E-PBM D82A-V84A could potentially be linked to glutamate excitotoxicity that we have previously observed in mice (Brison et al, 2011), possibly by interfering with PDZ-domain containing proteins found in neuronal cells (Feng and Zhang, 2009). We also demonstrate that HCoV-OC43 putative TMD plays a role in the neuropathogenesis following the CNS infection, albeit to a lesser extent than its PBM.…”
Section: Discussionmentioning
confidence: 79%
“…As HCoV-OC43 is naturally neuroinvasive and neurovirulent in mice (Brison et al, 2011;Desforges et al, 2014;Le Coupanec et al, 2015) and that the E protein is important for efficient propagation in neuronal cells (Figs. 3 and 4), we wished to investigate the importance of the two functional domains of E in the process of neuroinvasion.…”
Section: Fully Competent Hcov-oc43 E Protein Is Not Essential For Neumentioning
confidence: 99%
“…The increased cytokine production following infection by the S-mutant viruses may induce direct damage to neurons (Amor et al, 2010) and/or disturb glutamate homeostasis by down-regulating the glutamate transporter GLT-1 on astrocytes that should recapture the excess of glutamate, which may generate glutamate excitotoxicity (Carmen et al, 2009) and thereby contribute to neuronal degeneration (Fig. 4;Brison et al, 2011), which can be associated with hind-limb paralysis and possible demyelination Jacomy et al, 2010). The outcome of the observed degeneration of neurons may eventually be death of these essential cells.…”
Section: Mechanisms Of Hcov-induced Neurodegeneration: Possible Assocmentioning
confidence: 99%
“…To evaluate the potential role of DON treatment in mitigating glutamate excitotoxicity during SINV infection, glial cell markers associated with glutamate excitotoxicity during virus infection were examined (Brison et al, 2011; Darman et al, 2004). Expression of GFAP and GLT1 by astrocytes and IBA1 by microglial cells was assessed by immunohistochemistry (IHC) and immunoblot.…”
Section: Resultsmentioning
confidence: 99%